Esotericism in Botswana: Shamanism, Ancestral Reverence and New Age - Podolecka, Agnieszka 19XX- (Aries, 2022)
The article argues that “esotericism” can usefully be applied to a number of religious currents in Southern Africa. With a focus on Botswana, we survey a range of practices, from traditional “shamanic” healing to Pentecostal NRM s to New Age spiritualities and neoshamanism, some presented here for the first time. The term esotericism is useful for analysing the religious situation in Southern African contexts for three reasons. First, through a typological understanding of esotericism as initiation-based knowledge systems, we define one part of the landscape (usually termed “shamanism”) as constituting a form of “indigenous esotericism”. Second, through the European colonial expansion, this indigenous esotericism faced a violent rejection campaign that parallels the construction of “rejected knowledge” in Europe. While this forced many practices underground, they have resurfaced within Southern African Christianity. Third, “western” esoteric currents have recently been imported to Southern Africa and enter into dialogues with the “indigenous” forms.